Morphotectonic Analysis of South Solok Area: Implication for Geothermal Manifestation and Relative Tectonic Activity - Rina Sahara; Muhammad Fadhli; Ugi Kurnia Gusti (Journal of Geology Sriwijaya, 2022)
The distribution of geothermal energy in Indonesia reaches 40% of all Indonesia's geothermal reserves. Sapan Maluluang, South Solok is one of the areas that has a promising geothermal manifestation. This area has structural hills that surround the depression area which characterizes areas that have several geothermal surface manifestations. A combination of morphotectonic analysis and field observation of surface manifestation were used to understand the distribution of potential geothermal distribution in the study area. morphometric was carried out to analyze how the morphotectonic control in the research area used dem data input. Smf and Vf were used to understand the landscape evolution and tectonic control to the present morphological condition. In addition, field observation is carried out on how the condition of the source of manifestation found at the research site and observations of the lithology and geological structures control. In the dem data analysis, morphotectonic analysis elements were calculated, such as valley height-weight ratio (Vf) which resulted in 0.02 – 2.38 values of mountain front sinuosity (Smf) which had a value of 1.1-1.3. The research area is heavily controlled by active tectonics. Based on the results of field observation, it is known that there are 5 geothermal manifest sources in the form of hot springs which have a temperature of 175 ̊ C -185 ̊C and are controlled by the lithologies of the volcanic rocks of Mount Kerinci. In addition, from the lineament analysis at the research site, it was found that the NW-SE lineament was in the same direction as the Sumatran fault zone.